2022
DOI: 10.1186/s12870-022-03533-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reduced N-fertilizer application on foliar chemicals and functional qualities of tea plants under Toxoptera aurantii infestation

Abstract: Background The tea aphid, Toxoptera aurantii (Boyer de Fonscolombe) is a polyphagous pest predominant in tea orchards and has become the most pernicious pest deteriorating tea quality. Nitrogen (N) is essential to plant growth improvement, and it can significantly impact plant defensive ability against aphid infestation. This study was designed to quantify the influence of reduced N-fertilizer application on foliar chemicals and functional quality parameters of tea plants against the infestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Saturated alkanes (C13-C28) were also reported in previous studies as aphid cuticular hydrocarbons) from A. craccivora [52], Brevicoryne brassicae, Hyalopterus pruni [53], and Aphis fabae [54]). Decane (detected in E. lanigerum and A. punicae), 9-eicosene, and 8-heptadecene (detected in E. lanigerum) were detected in the headspace hydrocarbons (Figure 2, Table S2) and were also found by Muñoz, Argandoña [55], Ahmed, Agarwal [56], by Pokharel, Zhong [57] in aphid-infested plants, and by Ali, Morgan [58] in Leptothorax ants. Among Me-Alk, dimethyl alkanes were detected in the headspace of crushed aphids (Figure 2, Table S2), i.e., 3,8-dimethyl undecane, 4,7-dimethyl undecane, 4,5-dimethyl, nonane, and 4,6-dimethyl dodecane.…”
Section: Hydrocarbon Profiles As Biomarkers For Aphid Species Differe...mentioning
confidence: 88%
“…Saturated alkanes (C13-C28) were also reported in previous studies as aphid cuticular hydrocarbons) from A. craccivora [52], Brevicoryne brassicae, Hyalopterus pruni [53], and Aphis fabae [54]). Decane (detected in E. lanigerum and A. punicae), 9-eicosene, and 8-heptadecene (detected in E. lanigerum) were detected in the headspace hydrocarbons (Figure 2, Table S2) and were also found by Muñoz, Argandoña [55], Ahmed, Agarwal [56], by Pokharel, Zhong [57] in aphid-infested plants, and by Ali, Morgan [58] in Leptothorax ants. Among Me-Alk, dimethyl alkanes were detected in the headspace of crushed aphids (Figure 2, Table S2), i.e., 3,8-dimethyl undecane, 4,7-dimethyl undecane, 4,5-dimethyl, nonane, and 4,6-dimethyl dodecane.…”
Section: Hydrocarbon Profiles As Biomarkers For Aphid Species Differe...mentioning
confidence: 88%
“…[31][32][33] Until now, studies have focused on the individual components of tea aphids, ants, or natural enemies rather than examining the intricate interactions within the community. 34,26 A prior field study revealed that intercropped F. macrophylla significantly alleviated arthropod damages in a tea plantation. 35 Analyzing the potential effects of F. macrophylla as a trap plant on the networks associated with tea aphids would provide valuable insights into the complex dynamics of the arthropod community, leading to improved effectiveness of this strategy in tea plantations.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The tea aphid, Toxoptera aurantia, is a destructive and widespread pest in tea plantations. [24][25][26] It is estimated to cause more than 30% economic reduction in tea plantations in Zhejiang province, China. 25 Traditional treatments for tea aphids predominantly rely on chemical pesticides, exacerbating 3R issues (resistance, residue, and resurgence).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations